Kekerasan Verbal Istri pada Suami Perspektif Hukum Pidana: Studi Kasus di Dusun Srijaya Kelurahan Negara Aji Kecamatan Anak Tuha - Putri Ayu Lestari; Agus Setiawan; Habib Shulton A (CV. Ulil Albab Corp, 2023)
Domestic violence is a crime that occurs within the scope of the household. Acts of domestic violence are not only in the form of physical and sexual assault and neglect of the household. But there are also acts of verbal/psychological violence. Anyone can be a perpetrator or victim of verbal violence, verbal violence is violence that hurts the feelings of other people, because the perpetrators of this violence are often not aware of what they are doing. Victims of domestic violence are members of the household, including the wife's behavior towards her husband. As happened to a young couple in Srijaya Hamlet, Negara Aji Tua Village, Anak Tuha District, Central Lampung Regency, namely